2016
DOI: 10.1016/j.bbabio.2016.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Light-induced gradual activation of photosystem II in dark-grown Norway spruce seedlings

Abstract: Gymnosperms, unlike angiosperms, are able to synthesize chlorophyll and form photosystems in complete darkness. Photosystem I (PSI) formed under such conditions is fully active, but photosystem II (PSII) is present in its latent form with inactive oxygen evolving complex (OEC). In this work we have studied light-induced gradual changes in PSII function in dark-grown cotyledons of Norway spruce (Picea abies) via the measurement of chlorophyll a fluorescence rise, absorption changes at 830 nm, thermoluminescence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…The PSII as the heart of the photosynthetic process is highly sensitive to the environmental stresses. Its activity could be determined with one non-invasive time-resolved fluorescence measurement, which could measure the polyphasic rise with the basic steps of OJIP [43,[48][49][50][51][52][53][54]. Several studies have shown that the chlorophyll a transient has become one of the most popular tools to estimate stress-induced changes in photosynthetic performance.…”
Section: Discussionmentioning
confidence: 99%
“…The PSII as the heart of the photosynthetic process is highly sensitive to the environmental stresses. Its activity could be determined with one non-invasive time-resolved fluorescence measurement, which could measure the polyphasic rise with the basic steps of OJIP [43,[48][49][50][51][52][53][54]. Several studies have shown that the chlorophyll a transient has become one of the most popular tools to estimate stress-induced changes in photosynthetic performance.…”
Section: Discussionmentioning
confidence: 99%
“…Proteins were extracted from TM preparations by dilution in a buffer according to [ 25 ] and incubated for 30 min at 70 °C. SDS-PAGE was carried out using 8.5% focusing and 12% resolving polyacrylamide gel containing 0.1 % sodium dodecyl sulfate (SDS, Sigma-Aldrich).…”
Section: Methodsmentioning
confidence: 99%
“…Later, this fast PSI re‐oxidation was detected also in green alga Chlamydomonas reinhardtii and it was shown to be oxygen‐dependent, which indicated that Mehler type reaction is involved (Franck & Houyoux, ). Recently, this fast oxygen‐dependent PSI re‐oxidation upon dark‐to‐light transition was observed also in some representatives of gymnosperms (Shirao et al ., ; Pavlovič et al ., ).…”
Section: Introductionmentioning
confidence: 97%